2003
DOI: 10.1093/jmt/40.2.78
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Familiarity and Complexity on Appraisal of Complex Songs by Cochlear Implant Recipients and Normal Hearing Adults

Abstract: The purposes of this study were (a) to develop a test of complex song appraisal that would be suitable for use with adults who use a cochlear implant (assistive hearing device) and (b) to compare the appraisal ratings (liking) of complex songs by adults who use cochlear implants (n = 66) with a comparison group of adults with normal hearing (n = 36). The article describes the development of a computerized test for appraisal, with emphasis on its theoretical basis and the process for item selection of naturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 0 publications
5
71
0
3
Order By: Relevance
“…Due to limitations in the current state of technology, the cochlear implant device is constrained in its ability to code the spectrum of sound needed to perceive pitch and timbre (Galvin, Fu, & Nogaki, 2007;Sucher & McDermott, 2007). Not surprisingly, some cochlear implant users describe music as "hard to follow" and rate the sound of musical instruments as "emptier" than they would have expected a normal hearing listener to have perceived it (Gfeller, Witt, Woodworth, Mehr, & Knutson, 2002;Gfeller et al, 2003). In line with the suggestion that impaired perception may be a limiting factor in the appreciation of musical sound, several amusic individuals report difficulty in making sense of their perceptual experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to limitations in the current state of technology, the cochlear implant device is constrained in its ability to code the spectrum of sound needed to perceive pitch and timbre (Galvin, Fu, & Nogaki, 2007;Sucher & McDermott, 2007). Not surprisingly, some cochlear implant users describe music as "hard to follow" and rate the sound of musical instruments as "emptier" than they would have expected a normal hearing listener to have perceived it (Gfeller, Witt, Woodworth, Mehr, & Knutson, 2002;Gfeller et al, 2003). In line with the suggestion that impaired perception may be a limiting factor in the appreciation of musical sound, several amusic individuals report difficulty in making sense of their perceptual experience.…”
mentioning
confidence: 99%
“…In one scenario, if engagement and appreciation of music are dependent upon the listener having an intact representation of its intrinsic features, then we would expect that individuals with amusia would be unable to fully engage with and appreciate music. Cochlear implant users constitute one group of individuals for whom an impoverished perception of music's intrinsic features results in a negative impact on levels of music appreciation (e.g., Gfeller, Christ, Knutson, Witt, & Mehr, 2003;Leal et al, 2003). Due to limitations in the current state of technology, the cochlear implant device is constrained in its ability to code the spectrum of sound needed to perceive pitch and timbre (Galvin, Fu, & Nogaki, 2007;Sucher & McDermott, 2007).…”
mentioning
confidence: 99%
“…One major limiting–but not well‐studied–perceptual construct is sound quality. Sound quality is different from sound appraisal, which is a construct not consistently defined in the literature but often referred to as subjective pleasantness or likeability of a sound 1, 2, 3, 4, 5, 6, 7. Sound quality, in contrast, is defined here as the perceived richness of an auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Sound quality and sound appraisal may be related to each other in some cases, but not always; for example, perceived pleasantness of a sound does not necessarily correspond to high sound quality. While a number of studies have highlighted diminished sound appraisal in CI users,1, 2, 3, 8 sound quality perception remains relatively unexplored. The few studies that have focused on sound quality suggest that it is diminished in CI‐mediated listening relative to normal hearing (NH) listeners 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis 164 The data was analysed using SPSS version 16.0 to perform parametric and non- analysis because previous research showed that these two effects might influence the music 171 quality rating in NH and HI subjects [1,20,28]. Moreover, Pearson tests were separately used 172 to explore the relationship between hearing thresholds and music quality rating in HI 173 participants, respectively.…”
mentioning
confidence: 99%